Detection rate of SARS-CoV-2 RNA in relation to isolation time and environmental surface type - Sun, Weijie; Chen, Huimin; Tao, Shuan; Li, Na; Xu, Yao; Fang, Yewei; Chen, Luyan; Liang, Wei; Cao, Gang (Frontiers in Public Health, 2022)
Abstract Severe acute respiratory syndrome coronavirus (SARS-CoV-2) causes environmental contamination via respiratory droplets and persists on contaminants and environmental surfaces for anywhere from a few hours to 6 days. Therefore, it is particularly important to understand the transmission and containment of SARS-CoV-2 on the surface of objects within isolated environments. In this study, 356 environmental surface samples were collected and 79 tested positive, with the highest contamination rate (56.96%) in the wood category (bedside tables, wood floors, and wall). This study revealed differences in the detection rates of environmental surfaces in hospitalized and discharged rooms of patients with confirmed COVID-19 in 2 isolated settings (A: p=0.001; B: p=0.505), and suggested that environmental contamination may be an important route of virus transmission, providing a reference to guide regular cleaning and disinfection as well as effective suppression of virus transmission.